The Importance of Gender-Neutral Terminology in Risk Evaluation and Mitigation Strategy Programs: A Call to Action - Colin Burnette; William Smithy; Daniel Strock; Torunn E Sivesind; Robert Dellavalle (JMIR Publications, 2023)
The use of risk evaluation and mitigation strategy (REMS) programs is frequently required for prescriptions with potentially teratogenic effects, especially in the field of dermatology. Among these REMS programs, the most well-known example is isotretinoin, an oral retinoid that uses the iPLEDGE system. iPLEDGE has strict regulations and a lengthy approval process, and until recently, patients were grouped into 3 categories: male, female, or female of reproductive potential. This strict grouping has posed problems in the medical community, especially for gender-diverse individuals where their perceived gender conflates with their assigned grouping causing patient-specific distress. The distinction between gender-a multifactorial perception of identity-and biological sex is addressed under new iPLEDGE guidelines. Dermatologists now register patients under one of 2 categories: patients who can become pregnant and those who cannot become pregnant. This change simultaneously improves the accessibility to isotretinoin among gender-diverse individuals, while limiting prescription barriers. Despite initial success being limited due to lengthy system conversions, a registration process based on reproductive potential ultimately enhances iPLEDGE's goal to prevent potential birth defects. We propose that other REMS programs follow the standard set by the iPLEDGE system, including those for the medications thalidomide, acitretin, and mycophenolate mofetil, all of which currently have a similar taxonomy to that of the old iPLEDGE system. Implementing the standardization of gender-neutral terminology can maximize enrollment and minimize distress. Current and ongoing refinement of iPLEDGE and other REMS is needed to build protocols solely around the prevention of birth defects without regard to sex or gender.